Urgency of Targeted Advertising Transparency Regulation: A Comparative Study of the EU’s Digital Services Act and Indonesian Law - Sabina, Raisha Nurfairuz; Rosadi, Sinta Dewi; Priowirjanto, Enni Soerjati (Journal of Law, Politic and Humanities, 2025)
This research will discuss the urgency to regulate the transparency obligation of targeted advertising. Being the most popular method of marketing in today’s digital era, targeted advertising continuously becomes a target of controversy among consumers. Concern over targeted advertising ranges from the data collection process to how it is targeted towards consumers. This creates uncertainty among consumers due to the opacity of targeted advertising algorithms. Through a normative juridical method, this research will examine the adequacy of Indonesia’s regulations in addressing the issue of targeted advertising, ranging from the Consumer Protection Law, EIT Law, PSTE Regulation, and PMSE Regulation compared to the European Union’s Digital Services Act. This study will further discuss the urgency to comprehensively regulate the transparency of targeted advertising